Risky Behavior and Traffic Safety of Motorcycle Riders in Sungai Penuh City, Jambi Province - Abdul Kudus Zaini; Ahmad Ilham (Jurnal Intelek Dan Cendikiawan Nusantara, 2024)
Motorcycles are among the most popular means of transportation in Indonesia. However, traffic accidents remain a significant issue, particularly in the city of Sungai Penuh. A contributing factor to the high accident rate is the risky behavior exhibited by motorcycle riders. This study aims to investigate the impact of motorcycle riders’ risky behavior on traffic safety in Sungai Penuh City and to assess the level of traffic awareness among these riders. The research employed a quantitative method, utilizing data collected through questionnaires. The sample comprised 100 respondents from the Sungai Penuh community, selected through the random sampling technique. The questionnaire featured 24 statements categorized into two variables: risky behavior and traffic safety of motorcycle riders. Responses were measured using a Likert scale. For data analysis, a simple linear regression test was conducted to determine the relationship between the variables. The findings indicate that the risky behavior of motorcycle riders does not have a significant positive impact on traffic safety. Such behaviors account for 17.4% of traffic safety outcomes, while the remaining 82.6% is influenced by other factors, including environmental conditions, road quality, time of day, and driving conditions. Furthermore, the level of awareness among motorcycle riders regarding risky behavior and traffic safety is moderate. Common risky behaviors among motorcycle riders include not wearing helmets on short trips and riding at high speeds. Traffic safety practices that need improvement include regularly checking vehicle conditions and using protective gear such as gloves and shoes